Overview of Insulin Leaf Tea Administration on Blood Sugar People in Kemutug Kidul Village - Rizka Intan Amelia Putri; Endiyono Endiyono; Meida Laely Ramdani (CV. AFDIFAL MAJU BERKAH, 2026)
This study was initiated by the high incidence of hyperglycemia and the need for simple, safe, and easily implemented complementary therapies in the community. The aim of this study was to analyze the effectiveness of insulin leaf tea on blood glucose levels in the community in Kemutug Kidul Village. This study used a quasi-experimental design with a one-group pretest-posttest model. The population consisted of 36 diabetes mellitus sufferers, while the sample was selected using purposive sampling of 5 respondents. The research instruments included a glucometer, observation sheets, and intervention guidelines, while the data were analyzed descriptively by comparing pre- and post-intervention values. The results showed that all respondents experienced a decrease in blood glucose levels after consuming insulin leaf tea for 10 days, with an average decrease of 131.2 mg/dl. It was concluded that insulin leaf tea has the potential to be a non-pharmacological complementary therapy in helping control blood glucose, although this finding is still limited by the small sample size and the lack of a control group.